Efektivitas Proprioceptive Neuromuscular Facilitation pada pasien stroke: literature review - Zulia Putri Perdani; Endah Sri Rahayu (Health Sciences and Pharmacy Journal, 2021)
Stroke is a neurological disease that can cause loss of motor function in sufferers. A stroke causes the patient's motor skills to experience weakness, or hemiparesis. The purpose of this study is to determine the effectiveness of Proprioceptive Neuromuscular Facilitation in stroke cases. This research was a literature review. This article was obtained from two journal data bases, namely Sciencedirect and Google Scholar. The limitation of article search was published on January 2010-December 2020 with full text in Indonesian and English. The instrument used in this study was Crow Critical Apraissal Tolls (CCAT). There were 4,294 articles was conducted, then selected based on inclusion criteria and a critical appraisal and there were 6 articles matched with the criteria. These six articles used a pretest-posttest with control group design. From six articles were mentioned that Proprioceptive Neuromuscular Facilitation (PNF) exercises affect toward muscle strength, improve coordination, improve functional abilities and reduce mobility disorders in stroke patients. The conclusion is Proprioceptive Neuromuscular Facilitation is effective as an effort to treat stroke patients.